1997
DOI: 10.1007/s003380050080
|View full text |Cite
|
Sign up to set email alerts
|

Holocene sea level changes and reef development in the southwestern Indian Ocean

Abstract: The sedimentological and chronological study of Holocene reef sequences recovered in drill cores through modern reefs of Mauritius, Re´union Island and Mayotte allows the reconstruction of sea level changes and reef growth patterns during the Holocene. The branching-coral facies systematically predominates over coral head facies throughout the Holocene reef sequences, and Acropora is the main frame builder among the branching forms. The reconstructed sea level curves, based both on identification of coral asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 32 publications
8
114
0
1
Order By: Relevance
“…These results are broadly consistent with both wider Indo-Pacific (Cabioch et al, 1995, Camoin et al, 1997, Montaggioni, 2005 and Caribbean reefs (Neumann and Macintyre, 1985, A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT Hudson, 1998, Gischler andHudson, 2004), showing both initial vertical accretion and then lateral progradation of the reef flat in response to sea-level stabilisation and reduced accommodation. Differences in the precise timing of when these reefs first approached sea level and the transition to progradational growth at these locations (ranging from 6 ka to 2 ka) are related, in part, to differences in the timing of relative sea-level changes that result from glacial isostatic adjustment or tectonic movement (Lambeck et al, 2010).…”
Section: >>Figsupporting
confidence: 81%
“…These results are broadly consistent with both wider Indo-Pacific (Cabioch et al, 1995, Camoin et al, 1997, Montaggioni, 2005 and Caribbean reefs (Neumann and Macintyre, 1985, A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT Hudson, 1998, Gischler andHudson, 2004), showing both initial vertical accretion and then lateral progradation of the reef flat in response to sea-level stabilisation and reduced accommodation. Differences in the precise timing of when these reefs first approached sea level and the transition to progradational growth at these locations (ranging from 6 ka to 2 ka) are related, in part, to differences in the timing of relative sea-level changes that result from glacial isostatic adjustment or tectonic movement (Lambeck et al, 2010).…”
Section: >>Figsupporting
confidence: 81%
“…At sites on the mainland of southeast Africa, RSL reached~2.5 to 3.5 m above present by 6 ka [144]. Stable islands off the coast of southern Africa (Mauritius, Reunion and Mayotte) record no highstand (with RSL stabilizing at present level by 3 ka) because these small atoll islands subside with the ocean floor from hydro-isostatic loading [44,146,147]. A recent study of late Holocene RSL in the Seychelles [148], a location demonstrated to closely measure eustatic sea level [39], showed RSL rising <2 m in the last 2 ka.…”
Section: Africamentioning
confidence: 99%
“…The islands probably peaked at a height of 120-140 m above sea level at the Last Glacial Maximum (LGM, 25,000 years ago). Deglacial sea levels rose irregularly in stages to present, with a maximum oscillation at about 7000-6000 years BP, to about 1-3 m higher than present sea level (Camoin et al, 1984;Camoin et al, 1997). At that time Europa, Juan de Nova and Grande Glorieuse were not entirely submerged, but Tromelin undoubtedly and the Ile du Lys probably were.…”
Section: Origin Of the Native Floramentioning
confidence: 88%
“…This result is explained by the fact that they are young oceanic islands, geographically close to huge biodiversity reservoirs with comparable physical and abiotical conditions. Moreover, according to the available data (Camoin et al, 1984;Camoin et al, 1997;Virah-Sawmy et al, 2009;Woodroffe and Horton, 2005) the sea level has changed considerably since the likely formation of the Iles Eparses during the peak of the last interglacial, Marine Isotope Stage 5 (MIS5, 120,000 years ago). The islands probably peaked at a height of 120-140 m above sea level at the Last Glacial Maximum (LGM, 25,000 years ago).…”
Section: Origin Of the Native Floramentioning
confidence: 99%